ICT ADOPTION WITHIN MSMES USING TECHNOLOGY ACCEPTANCE MODEL - Siregar, Deboner H. H.; Ediraras, Dharma Tintri; Wulandari, Pandam Rukmi (Universitas Gunadarma, 2020)
The general objective of this study is to give a real portrait of ICT adoption in Micro, Small and Medium Enterprises (MSMEs) in Depok and Qingdao on 2011 by using Technology Acceptance Method (TAM) approach. This research is using primary data by distributing questionnaire and surveying the MSMEs directly. This research consist of 7 MSMEs from Qingdao and 46 MSMEs from Depok. There are perceived ease of ICT use-PEOU, perceived usefulness of ICT-PU, user attitude towards ICT-AT, strategic value of ICT-SV and acceptance towards ICT-ACC and all variables taken from the previous research. Path analysis and Independent sample T-test performed in this research to analyze the data and the result is PU is the key factor of MSMEs to adopt ICT and the ICT adoption within MSMEs in Qingdao is better than MSMEs in Depok.